Conservation Level Assessment Application to a heritage building - Rodrigues Fernanda; Matot Raquel; Costa Aníbal; Tavares Alíce; Fonseca Jorge; Alves Ana (MATEC Web of Conferences, 2019)
An evaluation methodology to estimate the envelope’s degradation level (DL) was developed being after object of adjustment and improvement. The methodology is based on visual survey and in the application of the Failure Mode and Effects Analysis (FMEA) method allied to evaluation scales, aiming to achieve building condition assessment and prioritizing refurbishment interventions. In Portugal, the high buildings number needing refurbishment justified the evolution and improvement of the original methodology of state of conservation assessment of residential buildings at controlled costs. This methodology firstly developed and applied for residential buildings was based on an evaluation scale of eight levels, which was after adjusted to five levels. This simplification aims an easier application of this methodology and provides users with a clear understanding of his features. A summarised evolution of this methodology will be depicted in this paper and will be applied to a heritage building located in the city of Oporto, in Portugal. Beyond the evolution of this buildings conservation assessment methodology, this paper aims to show its usefulness for heritage buildings condition assessment, through the application to a case study.